PENGARUH WAITING TIME SATISFACTION DAN SERVICE SATISFACTION TERHADAP LOYALITAS KONSUMEN NOKIA CARE di WTC MALL - Julindrastuti, Dijah (Equilibrium: Jurnal Ekonomi-Manajemen-Akuntansi, 2011)
Waiting is the work of the boring, throw julian, dam Creating Comfortable feeling is not regular. World Kesawan Marketing services in particular, there's always time waitng ON The shipping process. Benefits Service is any activity or the One offered Created shareholders party to the essentially intangible regular and regular APA does not produce any ownership. From the description on the top, then Author Title interested in taking RESEARCH "EFFECT OF SATISFACTION and WAITING FOR SERVICES TO CUSTOMER SATISFACTION loyalty in NOKIA CARE SURABAYA WTC." Husband RESEARCH aims (1) to determine the effect Simultaneously waiting time satisfaction and service satisfaction on customer loyalty Nokia Care WTC Surabaya mall. (2) To mrngetahui Partially influence of waiting time to satisfaction of customer loyalty Nokia Care mall WTC Surabaya. (3) To determine the effect of service satisfaction to customer loyalty Partially Nokia Care mall WTC Surabaya. (4) To determine the dominant influence among the waiting time satisfaction and loyalty to Nokia Care customer service satisfaction WTC Surabaya mall. RESEARCH husband using multiple linear regression analysis, the New Articles The results show that satisfaction with waiting time variable indicates the dominant influence on customer loyalty in the mall Nokia fence WTC Surabaya.